Respuesta :
To determine the effect of the radius changes to the coefficients, we need to rewrite the form of the equation into:
(x−α)²+(y−β)²=r²
From the equation, we will see that:
C=−α∗2
D=−β∗2
and α²+β²−r²=E
where r represents the radius of the circle and α,βare the coordinate of the center of the circle.
Therefore, when the r decreases the coefficients C and D do not change but E increases.
(x−α)²+(y−β)²=r²
From the equation, we will see that:
C=−α∗2
D=−β∗2
and α²+β²−r²=E
where r represents the radius of the circle and α,βare the coordinate of the center of the circle.
Therefore, when the r decreases the coefficients C and D do not change but E increases.
Answer: E. C and D unchanged,but E increases
Step-by-step explanation: